Understanding the adsorptive interactions of arsenate–iron nanoparticles with curved fullerene-like sheets in activated carbon using a quantum mechanics/molecular mechanics computational approach. Issue 22 (24th May 2017) - Ha, Nguyen Ngoc; Cam, Le Minh; Ha, Nguyen Thi Thu; Goh, Bee-Min; Saunders, Martin; Jiang, Zhong-Tao; Altarawneh, Mohammednoor; Dlugogorski, Bogdan Z.; El-Harbawi, Mohanad; Yin, Chun-Yang
Abstract : Incorporation of iron nanoparticles into activated carbon sheets greatly facilitates the chemisorption of HAsO4 2− . Abstract : The prevalence of global arsenic groundwater contamination has driven widespread research on developing effective treatment systems including adsorption using various sorbents. The uptake of arsenic-based contaminants onto established sorbents such as activated carbon (AC) can be effectively enhanced via immobilization/impregnation of iron-based elements on the porous AC surface. Recent suggestions that AC pores structurally consist of an eclectic mix of curved fullerene-like sheets may affect the arsenic adsorption dynamics within the AC pores and is further complicated by the presence of nano-sized iron-based elements. We have therefore, attempted to shed light on the adsorptive interactions of arsenate-iron nanoparticles with curved fullerene-like sheets by using hybridized quantum mechanics/molecular mechanics (QMMM) calculations and microscopy characterization. It is found that, subsequent to optimization, chemisorption between HAsO4 2− and the AC carbon sheet (endothermic process) is virtually non-existent – this observation is supported by experimental results. Conversely, the incorporation of iron nanoparticles (FeNPs) into the AC carbon sheet greatly facilitates chemisorption of HAsO4 2− . Our calculation implies that iron carbide is formed at the junction between the iron and the AC interface and this tightly chemosorbed layer prevents detachment of the FeNPs on the AC surface. Other aspects including electronic structure/properties, carbon arrangement defects and rate of adsorptive interaction, which are determined using the Climbing-Image NEB method, are also discussed.